Indonesia's Role in Combating Terrorism in Southeast Asia - Dewa Gede Sudika Mangku; Ni Putu Rai Yuliartini (Unnes Law Journal, 2021)
Terrorism is not a new issue but is an increasingly important issue for ASEAN countries, including Indonesia. Indonesia's involvement in the fight against terrorism is not only to fulfill its obligations as part of the international community to jointly fight terrorism, but also to fulfill its national interests. Indonesia's foreign policy in handling this issue puts forward cooperation with other countries, especially in ASEAN. Where in this study aims to know more about Indonesia's role in combating terrorism in the Southeast Asian region and to better understand the obstacles faced by Indonesia in combating terrorism in the Southeast Asian region. To achieve these objectives, this study uses a type of normative research with descriptive qualitative research methods. The data collection technique was carried out using the library research technique. Where the data comes from books, articles, journals and other documents. The results of the research show that terrorism is a security problem and a cross-border problem so that cooperation between ASEAN countries is needed to eradicate terrorism in Southeast Asia through the ASEAN Convention on Counter Terrorism. Indonesia's role in eradicating terrorism by internal and external efforts carried out bilaterally and multilaterally. Given that terrorism is a transnational crime, in Indonesia's role in eradicating terrorism there are several obstacles and challenges. This challenge relates to the principles of consensus and non-intervention, domestic conflicts as well as differences in commitments and perceptions among ASEAN countries.